2005
DOI: 10.1002/chem.200400835
|View full text |Cite
|
Sign up to set email alerts
|

3‐Fluoropiperidines and N‐Methyl‐3‐fluoropiperidinium Salts: The Persistence of Axial Fluorine

Abstract: It has previously been shown that the fluorine atom in N-protonated 3-fluoropiperidine salts in water strongly prefers the axial orientation in the six-membered ring chairs. In the present work we examine the proposition that the N-methyl salts are equally disposed to present axial fluorine. Initially, we explored this point by comparing the structures of the corresponding NH2+, NHMe+, and NMe2+ salts by means of density functional theory (DFT), ab initio, and MMFF force field calculations with and without aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 51 publications
2
51
0
Order By: Relevance
“…Little recognized is the phenomenon that the charge in an N-methyl cation is not localized on nitrogen, but leaks out onto the hydrogens on carbon. Therefore, each of these hydrogens bears a positive charge of approximately 0.2 to 0.3 (Sun et al, 2005). Thus, in the NR2A receptor, the negatively charged carboxylates of the Glu394 (not shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Little recognized is the phenomenon that the charge in an N-methyl cation is not localized on nitrogen, but leaks out onto the hydrogens on carbon. Therefore, each of these hydrogens bears a positive charge of approximately 0.2 to 0.3 (Sun et al, 2005). Thus, in the NR2A receptor, the negatively charged carboxylates of the Glu394 (not shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…According to earlier studies for compounds containing the F-C-C-N + fragment [8][9][10][27][28][29][30][31], the preferred gauche arrangement along this fragment has strong contribution from the electrostatic attraction between the electronegative fluorine substituent and the positively charged nitrogen. According to NBO analysis, the gauche conformers are far more stabilized by hyperconjugation than the anti geometries (Table 1), whose important contribution comes from r CH ?…”
Section: Resultsmentioning
confidence: 96%
“…[3][4][5][6] They established that there is a strong preference (calculated energy difference of 4.0-5.4 kcal mol À1 between the gas-phase anti and gauche conformations) for the structures with the fluorine atom in the axial position (1 a/ 2 a) over those with the fluorine atom in the equatorial position (1 b/2 b; Scheme 1). [5] In our computational studies, we have explored the conformational preferences of bfluoroethylamine (3) and its protonated counterpart bfluoroethylammonium (4).[7] Our density functional theory (DFT) calculations indicated that there is no intrinsic gauche effect for the neutral amine 3; the neutral molecule only prefers a gauche conformation because there is a weakly stabilizing intramolecular NÀH···FÀC hydrogen bond. When the nitrogen atom is formally charged in 4, however, the bfluoroethylammonium cation displays a very strong preference (5.8 kcal mol À1 ) for the gauche conformation (4 a).…”
mentioning
confidence: 98%
“…The gauche conformation is strongly preferred when the functional group is cationic. [5,7] Angewandte Chemie Mulliken charge densities for 10 indicated that the pyridinium nitrogen atom has a + 0.29 charge, whereas the adjacent ortho carbon (+ 0.01) and hydrogen (+ 0.12) atoms carry a significantly less-positive charge. This situation is the reverse of that, for example, in alkylammonium (…”
mentioning
confidence: 98%
See 1 more Smart Citation